Packaging materials and packaging bags

A packaging material with specific resin compositions and controlled glass transition temperature differences addresses the challenges of recyclability, heat sealability, and oxygen barrier properties, enhancing its overall performance.

JP7619340B2Active Publication Date: 2025-01-22TOYO INK MFG CO LTD
6 Cites 0 Cited by

Patent Information

Application Number
JP2022127510
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-08-10
Publication Date
2025-01-22
Estimated Expiration
2042-08-10

AI Technical Summary

Technical Problem

Existing packaging materials face challenges in achieving high recyclability, heat sealability, low foreign object count, blocking resistance, and oxygen barrier properties, particularly due to the use of petroleum-derived plastics and the limitations of polyethylene and nitrocellulose resins.

Method used

A packaging material comprising a heat seal layer with acrylic resin and/or ethylene-vinyl acetate copolymer resin, a barrier layer with vinyl alcohol or ethylene-vinyl alcohol copolymer resin, and a surface protective layer with styrene-acrylic copolymer resin, where the glass transition temperature difference between the seal and protective layers is controlled to enhance properties.

Benefits of technology

The solution provides packaging materials with excellent heat sealability, recyclability, low foreign matter, blocking resistance, and oxygen barrier properties, improving overall performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007619340000001
    Figure 0007619340000001
  • Figure 0007619340000002
    Figure 0007619340000002
  • Figure 0007619340000003
    Figure 0007619340000003
Patent Text Reader

Abstract

To provide a packaging material excellent in a heat-sealing property, a recyclability, a low foreign matter count, a blocking resistance, and an oxygen barrier property.SOLUTION: There is provided a packaging material that sequentially has a heat-seal layer, a barrier layer, a paper base material, and a surface protection layer, wherein the heat-seal layer contains an acrylic resin and / or an ethylene-vinyl acetate copolymer resin, and a coating amount of the heat-seal layer is 1 to 18 g / m2, and the surface protection layer contains a styrene-acrylic copolymer resin (B).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a packaging material and a packaging bag. [Background technology]

[0002] In recent years, it has become common for product packages and other wrapping materials to be printed for decoration and surface protection. Furthermore, the quality of printing, such as the design, beauty, and luxury of the printed matter, can stimulate consumer purchasing motivation, and is therefore of great industrial value.

[0003] Generally, plastic films are mainly used to construct packages, and since they are transparent, there are also usage methods that allow the contents to be visually confirmed, and laminated packaging materials have been used in particular. For example, Patent Document 1 describes an invention of a laminated packaging material consisting of a base material, a printing layer, an adhesive layer, and a sealant layer, in which biomass resin is used in the printing layer and the adhesive layer. However, laminated packaging materials originally use a large amount of petroleum-derived plastic film. Therefore, there is a demand for packaging materials that are environmentally friendly, carbon neutral, and can further reduce the amount of plastic used, and technological developments are being made.

[0004] For example, Patent Document 2 describes an invention relating to a packaging material having a surface protective layer, a printing layer, a paper substrate layer, and a resin layer in this order, the resin layer being a polyethylene resin, and the surface protective layer being a nitrocellulose resin. However, the polyethylene must be thickened in the resin layer to ensure heat sealability, so that about half of the packaging material weight is polyethylene. From the viewpoint of recyclability, it is preferable that the paper content in the packaging material is high, but in the above invention, it is presumed that there is a problem with heat sealability when the heat seal layer is applied in a low amount. In addition, when polyethylene is heated and melted onto the paper substrate, the polyethylene solidifies in a state in which it incorporates a part of the paper substrate. Polyethylene has excellent alkali resistance and water resistance, and does not dissolve in the waste paper recovery process, so there are problems with recyclability and low number of foreign matter. Furthermore, since the surface protective layer is a nitrocellulose resin, there are problems with blocking resistance and low number of foreign matter. In addition to solving the above problems, it is necessary to improve the blocking resistance and oxygen barrier properties required for packaging materials.

[0005] Therefore, a satisfactory packaging material having excellent heat sealability, recyclability, low foreign matter content, blocking resistance and oxygen barrier properties has not yet been found. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2018-051796 A [Patent Document 2] JP 2020-55171 A Summary of the Invention [Problem to be solved by the invention]

[0007] An object of the present invention is to provide a packaging material that has excellent heat sealability, low foreign matter count, blocking resistance and oxygen barrier properties while maintaining the recyclability of paper, and a packaging bag using the same. [Means for solving the problem]

[0008] As a result of extensive research into the above problems, the present inventors have found that the above problems can be solved by using the packaging material described below, and have thus completed the present invention.

[0009] That is, the present invention provides a packaging material having a heat seal layer, a barrier layer, a paper substrate, and a surface protective layer, The heat seal layer contains an acrylic resin (A) and / or an ethylene-vinyl acetate copolymer resin, and the coating amount of the heat seal layer is 1 to 18 g / m 2 and The present invention relates to a packaging material, wherein the surface protective layer contains a styrene-acrylic copolymer resin (B).

[0010] The present invention also relates to the above packaging material, wherein the glass transition temperature Tg(C) of the surface protective layer is higher than the glass transition temperature Tg(D) of the heat seal layer, and the difference between Tg(C) and Tg(D) is 10°C or more.

[0011] The present invention also relates to the above packaging material, wherein the surface protective layer further contains a hydrocarbon wax.

[0012] The present invention also relates to the above packaging material, wherein the hydrocarbon wax has a hardness (penetration) of 0.5 to 12 at 25° C. as specified by JIS K2207.

[0013] The present invention also relates to the above packaging material, wherein the barrier layer is disposed opposite the heat seal layer to the paper substrate.

[0014] The present invention also relates to the above packaging material, wherein the barrier layer contains a vinyl alcohol resin and / or an ethylene-vinyl alcohol copolymer resin.

[0015] The present invention also relates to the above packaging material, wherein the content of the paper base material in the total amount of the packaging material is 50% by mass or more.

[0016] The present invention also relates to a packaging bag formed from the above packaging material.

[0017] The present invention also provides a method for producing a packaging material having a heat seal layer, a barrier layer, a paper base material, and a surface protective layer, comprising the steps of: A heat seal agent containing an acrylic resin (A) and / or an ethylene-vinyl acetate copolymer resin is applied to one side of a paper substrate having a barrier layer, and the coating amount is 1 to 18 g / m. 2 forming a heat seal layer; and applying an overcoat agent containing a styrene-acrylic copolymer resin (B) onto the other side of the paper base material having the barrier layer to form a surface protective layer. Effect of the Invention

[0018] According to the present invention, it is possible to provide a packaging material and a packaging bag that are excellent in heat sealability, recyclability, low foreign matter count, blocking resistance, and oxygen barrier property. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] The following describes in detail the embodiments of the present invention. However, the following description of the components is merely an example of an embodiment of the present invention, and the present invention is not limited to these contents as long as it does not deviate from the gist of the present invention.

[0020] In the following description, unless otherwise specified, "parts" refers to "parts by mass" and "%" refers to "% by mass." In addition, the packaging material may be referred to as a "laminate," but this has the same meaning. In addition, "printing ink" refers to ink containing pigments and other colorants for forming a printed layer. "Overcoat agent" refers to a coating agent that does not contain pigments or other colorants for forming a surface protective layer, but does not exclude traces of colorants that are unintentionally mixed in.

[0021] [Packaging material] A packaging material having a heat seal layer, a barrier layer, a paper base material, and a surface protective layer, wherein the heat seal layer contains an acrylic resin (A) and / or an ethylene-vinyl acetate copolymer resin, and the coating amount of the heat seal layer is 1 to 18 g / m 2 and the surface protective layer comprises a styrene-acrylic copolymer resin (B).

[0022] [Heat seal layer] <Heat sealant> The heat seal layer in the present application is formed by coating a heat seal agent, which contains an acrylic resin (A) and / or an ethylene-vinyl acetate copolymer resin, and further contains a solvent. The heat seal agent may also contain other resins and additives. From the viewpoint of environmental load, the solvent is preferably aqueous. From the viewpoint of printability, the viscosity of the heat seal agent is preferably 20 to 200 mPa s.

[0023] The resin contained in the heat sealing agent may include, in addition to the acrylic resin (A) and / or the ethylene-vinyl acetate copolymer resin, a urethane resin, a polyethylene resin, a polypropylene resin, etc. These may be used alone or in combination of two or more kinds.

[0024] The content of the resin in the heat seal layer is preferably 80 to 100% by mass, and more preferably 90 to 100% by mass, based on 100% by mass of the heat seal layer. When it is in the above range, the heat sealability is good.

[0025] The tensile strength of the resin in the heat seal layer is 98 to 270 kg / cm 2 is preferably 130 to 240 kg / cm 2 More preferably, it is 160 to 200 kg / cm 2It is particularly preferable that the elongation of the resin is 650 to 900%, more preferably 700 to 850%, and particularly preferably 750 to 800%. The hardness (Shore hardness) of the resin is preferably 17 to 38, more preferably 21 to 34, and particularly preferably 25 to 30. When the tensile strength, elongation, and hardness are within the above ranges, the heat seal layer has a good balance between hardness and flexibility, making it possible to achieve both heat sealability and blocking resistance.

[0026] <Measurement of tensile strength and elongation> In this application, tensile strength is the force required to stretch a plastic test specimen to break, and elongation is the ratio of the length of the plastic test specimen when it breaks to the original length of the test specimen. Tensile strength and elongation are measured according to ASTM D638.

[0027] <Hardness (Shore hardness)> In the present application, the hardness (Shore hardness) is the indentation depth when an indenter is pressed in. The hardness (Shore hardness) is measured using a digital Shore hardness tester TIME5431 (manufactured by TIME Corporation) in accordance with ISO-868.

[0028] <Acrylic resin (A)> The acrylic resin (A) is a resin containing a structural unit derived from an acrylic monomer. The acrylic resin (A) preferably has a carboxyl group or other acidic group. The acid value of the acrylic resin (A) is preferably 20 to 120 mgKOH / g, more preferably 30 to 100 mgKOH / g, and particularly preferably 40 to 80 mgKOH / g. When the acid value of the acrylic resin (A) is 20 mgKOH / g or more, the recyclability is good, and when it is 120 mgKOH / g or less, the blocking resistance is good. The glass transition temperature of the acrylic resin (A) is preferably -40 to 10°C, more preferably -30 to 5°C, and particularly preferably -20 to 0°C. When the glass transition temperature of the acrylic resin (A) is in the above range, the blocking resistance and heat sealability are good.

[0029] Suitable examples of the acrylic resin (A) include a homopolymer of an acrylic monomer, a copolymer of an acrylic monomer and an acidic monomer, and a copolymer of ethylene and an acrylic monomer. From the viewpoint of blocking resistance, a copolymer of ethylene and an acrylic monomer is preferred.

[0030] Examples of the monomer containing the (meth)acrylic monomer include alkyl ester compounds of (meth)acrylic acid, such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, n-hexyl (meth)acrylate, n-octyl (meth)acrylate, decyl (meth)acrylate, and lauryl (meth)acrylate; (meth)acrylic acid amide derivatives containing at least one N-substituted methylol group, such as N-methylol (meth)acrylamide; Aminoalkyl esters of (meth)acrylic acid such as dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, dipropylaminoethyl (meth)acrylate, dimethylaminopropyl (meth)acrylate, diethylaminopropyl (meth)acrylate, and dipropylaminopropyl (meth)acrylate; Mono- or diesters of (meth)acrylic acid of glycols such as diethylene glycol and dipropylene glycol, Styrene, α-methylstyrene and other styrene derivatives, Hydroxyalkyl ester compounds of (meth)acrylic acid, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and 3-hydroxypropyl (meth)acrylate; Acrylic acid, methacrylic acid, Examples of suitable vinyl compounds include those having an acid group such as maleic acid and itaconic acid. From the viewpoint of heat sealability, the acrylic resin (A) preferably has a carboxyl group and / or a hydroxyl group, and when the acrylic resin (A) has a hydroxyl group, it preferably contains a hydroxyalkyl ester compound of (meth)acrylic acid as a monomer constituting the acrylic resin (A).

[0031] The acrylic resin (A) may be a commercially available product, for example, JONCRYL PDX7356, PDX-7326, PDX-7430 manufactured by BASF, PE-1126, JE-1113, KE1148 manufactured by Seiko PMC Corporation, AC-3100 manufactured by Japan Coating Resins Co., Ltd., etc.

[0032] <Ethylene-vinyl acetate copolymer resin> The ethylene-vinyl acetate copolymer resin is a copolymer made of ethylene and vinyl acetate. The vinyl acetate content in the ethylene-vinyl acetate copolymer resin is preferably 5 to 50 mass%, more preferably 10 to 40 mass%, and particularly preferably 20 to 30 mass%, based on 100 mass% of the ethylene-vinyl acetate copolymer resin. The minimum film-forming temperature of the ethylene-vinyl acetate copolymer resin is preferably 40 to 120°C, and more preferably 60 to 100°C. When the vinyl acetate content and the minimum film-forming temperature are within the above ranges, the heat sealability is good. The glass transition temperature of the ethylene-vinyl acetate copolymer resin is preferably -60 to 20°C, more preferably -25 to 5°C, and particularly preferably -20 to -10°C.

[0033] Examples of the ethylene-vinyl acetate copolymer resin that can be used include Aquatex EC series manufactured by Japan Coating Resins Co., Ltd., and Sumikaflex S-201HQ, S-305, S-305HQ, S-328HQ, S-400HQ, S-401HQ, S-408HQE, S-410HQ, S-450HQ, S-455HQ, S-456HQ, S-460HQ, S-467HQ, S-470HQ, S-480HQ, S-510HQ, S-520HQ, S-752, and S-755 manufactured by Sumitomo Chemical Co., Ltd.

[0034] <<Acid value measurement>> In the present application, the acid value is the number of milligrams of potassium hydroxide required to neutralize the acidic groups contained in 1 g of resin solid content, and is measured in accordance with JIS K0070.

[0035] <<Measurement of glass transition temperature>> In the present application, the glass transition temperature was measured by simultaneous thermogravimetry and differential thermal analysis (TG-DTA) using a DTG-60A manufactured by Shimadzu Corporation. In detail, the glass transition temperature was determined as the inflection point temperature in the baseline shift under the conditions of a nitrogen atmosphere, a measurement temperature range of −100 to 200° C., and a heating rate of 1° C. / min.

[0036] <Measurement of weight average molecular weight> In the present application, the weight average molecular weight (Mw) can be measured, for example, by GPC (gel permeation chromatography). In the case of aqueous resins, the molecular weight can be calculated using polyethylene glycol as a standard substance, and the measuring device can be a GPC device such as Shodex GPC-401 manufactured by Showa Denko K.K., and the column can be a Shodex OHpak LB-805 manufactured by Showa Denko K.K., etc. Examples of detectors include RI (differential refractometer), and the measurement temperature is preferably 20 to 50°C for the column temperature. Examples of eluents include 0.1N NaNO3 aqueous solution, and the flow rate is 0.2 to 5 mL / min. In the case of oil-based resins, the molecular weight can be calculated using polyethylene glycol as a standard substance, and the measuring device can be a GPC device such as Shodex GPC-104 manufactured by Showa Denko K.K., and the column can be a Shodex LF-404 manufactured by Showa Denko K.K., etc. The detector can be an RI (differential refractometer), and the measurement temperature is preferably a column temperature of 20 to 50° C. The eluent can be tetrahydrofuran, etc., and the flow rate is 0.2 to 5 mL / min.

[0037] <Measurement of minimum film-forming temperature> In the present application, the temperature measured in accordance with JIS K 6828-1:2003 using a TP-801MFT tester manufactured by Tester Sangyo Co., Ltd. was defined as the minimum film-forming temperature.

[0038] <Additives> The heat seal layer may further contain optional additives such as an antifoaming agent, an emulsifier, a preservative, a plasticizer, an amide wax, a hydrocarbon wax, and a chelating crosslinking agent, and preferably contains an antifoaming agent and / or an emulsifier.

[0039] Defoaming Agent In the present application, it is preferable to include an antifoaming agent, and when an antifoaming agent is included, the smoothness of the heat seal layer is improved, and the heat seal strength is improved. The antifoaming agent may be a silicon-based antifoaming agent or a non-silicon-based antifoaming agent, and from the viewpoint of antifoaming properties, a silicon-based antifoaming agent is preferable. The content of the antifoaming agent in the heat seal layer is preferably 0.01 to 1 mass%, more preferably 0.05 to 0.5 mass%, and particularly preferably 0.1 to 0.3 mass%, based on 100 mass% of the heat seal layer.

[0040] The defoaming agent may be a commercially available product, for example, BYK-024, BYK-025, BYK-028, etc. manufactured by BYK.

[0041] "emulsifier" In the present application, it is preferable to include an emulsifier. When an emulsifier is included, the solubility in water is improved, and thus the recyclability and the number of foreign matters are improved. Examples of the emulsifier include vinyl alcohol resin, ethylene-vinyl alcohol copolymer resin, nonionic surfactant, cationic surfactant, anionic surfactant, etc., and from the viewpoint of recyclability, vinyl alcohol resin and cationic surfactant are preferable. The content of the emulsifier in the heat seal layer is preferably 0.01 to 1 mass %, more preferably 0.05 to 0.5 mass %, and particularly preferably 0.1 to 0.3 mass %, based on 100 mass % of the heat seal layer.

[0042] <Formation of heat seal layer> The heat seal layer in the present invention is located on the opposite side of the paper substrate from the side having the surface protective layer. The method for forming the heat seal layer can be appropriately selected from known printing methods such as gravure printing and flexographic printing, and is preferably flexographic printing. The coating amount of the heat seal layer is 1 to 18 g / m 2 and 3 to 12 g / m 2 It is preferable that the thickness is 4 to 8 g / m 2 When it is in the above range, the heat sealability and blocking resistance are excellent.

[0043] The heat seal layer can be formed, for example, by printing the heat seal agent on the paper substrate surface opposite to the surface protective layer, and then drying and removing the volatile components. As the printing method, gravure printing and flexographic printing are suitable. For example, in gravure printing, the agent is diluted with a diluting solvent to an appropriate viscosity and concentration as necessary, and is supplied to each printing unit alone or in a mixture, and then applied, and the coating is fixed by drying in an oven to obtain a heat seal layer.

[0044] (gravure printing) << Gravure version >> In gravure printing, the gravure plate is a cylindrical metal plate on which recesses for each color are formed by engraving, etching, or laser. There are no restrictions on the use of engraving and laser, and they can be set arbitrarily according to the pattern. Lines of 80 to 250 are used appropriately, and the higher the line count, the finer the printing.

[0045] Gravure printing machine In a gravure printing press, one printing unit is equipped with the gravure plate and doctor blade. There are many printing units, and each unit has an oven drying unit. Printing is performed by rotary printing, and a roll-to-roll printing method is used. The type of plate and the type of doctor blade are appropriately selected according to the specifications.

[0046] [Barrier layer] The packaging material and packaging bag of the present application have a barrier layer for imparting barrier properties. The barrier layer exists to control the permeation of objects to be blocked, such as light, magnetism, and various gases, through the packaging material, and contains a barrier component. The barrier layer may be a paper substrate having a barrier layer on the heat seal layer side, a paper substrate having a barrier layer on the surface protective layer side, or a paper substrate containing a barrier resin, and a paper substrate having a barrier layer on the heat seal side is preferred. Note that in the case of a paper substrate containing a barrier resin, the barrier layer does not form a flat layer in a state where the barrier resin that is the barrier layer has permeated into the paper substrate, but the barrier resin exists as a continuous phase separate from the paper substrate and can be confirmed as a barrier layer. In the present application, preferred forms of the barrier layer include a form on the heat seal layer side of the paper substrate, a form on the surface protective layer side of the paper substrate, and a form in which the paper substrate has barrier properties and functions as a barrier layer, and a more preferred form is a form on the heat seal layer side of the paper substrate. In the above cases, the heat seal layer is prevented from seeping into the paper during the formation of the heat seal layer, resulting in good heat sealability. When the paper substrate functions as a barrier layer, this refers to a state in which the paper substrate contains a barrier component and thereby exhibits barrier properties, and the barrier component may be present uniformly or non-uniformly in the paper substrate.

[0047] The barrier layer can be formed by vapor deposition, lamination, T-die casting, or coating and drying the barrier component in a liquid form. Examples of the barrier component include metal compounds such as aluminum, silica, and alumina, and barrier resins such as polyvinylidene chloride resin, polyamide resin, vinyl alcohol resin, ethylene-vinyl alcohol copolymer resin, and barrier nylon resin (MXD). It is preferable to include vinyl alcohol resin and ethylene-vinyl alcohol copolymer resin. When the barrier layer is a vinyl alcohol resin or ethylene-vinyl alcohol copolymer resin, the solubility in water is high, so that recyclability and the number of foreign matter are good. The barrier layer may be a single layer or a multilayer structure, and may contain two or more types of compounds in one layer.

[0048] <Vinyl alcohol resin> The polyvinyl alcohol resin can be prepared as a solution, for example, and laminated on a paper substrate by coating and drying the solution to form a barrier layer. The saponification degree of the vinyl alcohol is preferably 40 to 100 mol %. The coating amount of the vinyl alcohol resin is preferably 1 to 24 g / m 2 is preferably 3 to 12 g / m 2 When the saponification degree and the coating amount are within the above ranges, the barrier property is good.

[0049] Examples of the vinyl alcohol resin include Kuraray Poval LM-20SO (manufactured by Kuraray Co., Ltd.) and Gohsenol NM-14 (manufactured by Nippon Synthetic Chemical Industry Co., Ltd.).

[0050] Ethylene-vinyl alcohol copolymer resin The ethylene-vinyl alcohol copolymer resin can be prepared, for example, in a solution, and then the solution is coated and dried to form a barrier layer on a paper substrate. The ethylene content of the ethylene-vinyl alcohol copolymer resin is preferably 25 to 50 mol %. The coating amount of the ethylene-vinyl alcohol copolymer resin is preferably 1 to 20 g / m. 2 It is preferable that the thickness is 3 to 10 g / m 2 When the ethylene content and the coating amount are within the above ranges, the barrier property is good.

[0051] Examples of the ethylene-vinyl alcohol copolymer resin include EVAL EP-F101 (manufactured by Kuraray Co., Ltd.) and Soarnol D2908 (manufactured by Nippon Synthetic Chemical Industry Co., Ltd.).

[0052] The barrier layer may further have an easy-adhesion layer. The easy-adhesion layer preferably contains at least one selected from the group consisting of a polyurethane resin layer, an acrylic resin (which may be the same as or different from the above-mentioned acrylic resin (A)), a polyester resin, and a vinyl alcohol resin, and more preferably contains the resin that is water-based. The easy-adhesion layer can be formed by printing or other known methods.

[0053] <Method of applying and drying in liquid form> The barrier component can be dissolved or dispersed in a volatile component, and then coated and dried in a liquid form, for example, by coating the substrate with a printer or the like, and then removing the volatile component. Examples of the coating method include known printing methods such as gravure printing and flexographic printing. For example, the barrier layer can be obtained by diluting the composition with a diluting solvent to a viscosity and concentration suitable for gravure printing as necessary, supplying the composition alone or in a mixture to each printing unit, applying the composition, and then fixing the coating by drying in an oven.

[0054] Vapor Deposition Method Suitable examples of the vapor deposition method include physical vapor deposition methods (PVD methods) such as vacuum deposition, sputtering, and ion plating, and chemical vapor deposition methods (CVD methods) such as plasma chemical vapor deposition, thermal chemical vapor deposition, and photochemical vapor deposition.

[0055] (Vacuum deposition method) The vacuum deposition method is a method of depositing metal compounds such as aluminum, silica, and alumina at 1200 to 1500°C for 10 minutes by high-frequency induction heating, direct current heating, or electron beam heating. -1 ~10 -2 This method involves deposition under conditions of about Pa. Prior to vacuum deposition, the surface of the object to be deposited can be treated to improve adhesion by corona discharge treatment or the like.

[0056] (Sputtering method) The sputtering method involves depositing metal compounds such as aluminum, silica, and alumina at 10 -1 ~10 -2 This is performed by introducing an inert gas such as Ar under conditions of about Pa and applying a voltage.

[0057] <Barrier resin> Examples of the barrier resin contained in the paper base material include cellophane, vinyl alcohol resin, ethylene-vinyl alcohol copolymer resin, paraffin resin, acrylic resin (which may be the same as or different from the above-mentioned <acrylic resin (A)>), rosin resin, and epoxy resin, and vinyl alcohol resin and ethylene-vinyl alcohol copolymer resin are preferred. These may be used alone or in combination of two or more.

[0058] [Paper base material] The paper substrate is not particularly limited, and any known paper substrate can be used. Examples of such paper substrates include medium-quality paper, fine paper, newsprint, various coated papers, lining paper, impregnated paper, cardboard, art paper, cast paper, kraft paper, coated board, ivory paper, card paper, cup base paper, cast paper, light-shielding paper, and surface-treated paper substrates thereof. The basis weight of the paper base material is preferably 50 to 150 g / m 2 , more preferably 55 to 120 g / m 2 , more preferably 60 to 90 g / m 2 It is.

[0059] [Surface protection layer] In the present application, the surface protective layer contains a styrene-acrylic copolymer resin (B) and is located on the opposite side of the paper substrate to the side having the heat seal layer. The surface protective layer can be formed by an overcoat agent containing a styrene-acrylic copolymer resin (B), and the formation method can be appropriately selected from known printing methods such as gravure printing and flexographic printing, and is preferably flexographic printing. In the present application, the "overcoat agent" refers to one that does not contain a colorant such as a pigment, but does not exclude one that contains a small amount of colorant that has been unintentionally mixed in. The coating weight of the surface protective layer is 1.5 to 12 g / m 2 is preferably 3 to 7 g / m 2 The coating weight of the surface protective layer is 1.5 g / m 2 When the coating amount is 12 g / m or more, the uniformity of the surface protective layer is improved, so that the gloss, heat resistance, and blocking resistance are good. 2 When it is equal to or less than this, the amount of the residual solvent in the surface protective layer is reduced, and therefore blocking resistance is improved.

[0060] <Styrene-acrylic copolymer resin (B) contained in the surface protective layer> The styrene-acrylic copolymer resin (B) is preferably an aqueous resin, which may be either a water-soluble resin or an aqueous emulsion resin, but is preferably an aqueous emulsion resin.

[0061] The styrene-acrylic copolymer resin (B) preferably has an acid group, and in this case, the acid value is preferably 20 to 200 mgKOH / g, more preferably 30 to 150 mgKOH / g, and even more preferably 80 to 120 mgKOH / g. When the styrene-acrylic copolymer resin (B) has an acid group and the acid value is within the above range, the recyclability and the number of foreign matter are good. The weight average molecular weight of the styrene-acrylic copolymer resin (B) is preferably 2000 to 600000, more preferably 50000 to 600000, and particularly preferably 70000 to 600000. The glass transition temperature of the styrene-acrylic copolymer resin (B) is preferably -20 to 80°C, more preferably -10 to 60°C, and even more preferably 0 to 40°C. When the weight average molecular weight and glass transition temperature of the styrene-acrylic copolymer resin (B) are within the above ranges, the blocking resistance is good.

[0062] The tensile strength of styrene-acrylic copolymer resin (B) is 630-770kg / cm 2 It is preferable that the viscosity is 655 to 745 kg / cm 2More preferably, it is 680 to 720 kg / cm 2 It is particularly preferable that the elongation of the resin is 1 to 20%, more preferably 1.5 to 10%, and particularly preferably 2 to 5%. The hardness (Rockwell hardness) of the resin is preferably M70 to M85, more preferably M73 to M82, and particularly preferably M76 to M79. When the tensile strength, elongation, and hardness are within the above ranges, the balance between hardness and flexibility of the surface protective layer is good, and it is possible to achieve both recyclability, a low number of foreign matter, and blocking resistance.

[0063] <Hardness (Rockwell hardness)> In the present application, hardness (Rockwell hardness) is the indentation depth when an indenter is pressed in. Hardness (Rockwell hardness) is measured in accordance with ASTM D785 using a portable hardness tester (manufactured by Mitutoyo Corporation).

[0064] <Resins other than styrene-acrylic copolymer resin (B) that may be used in the surface protective layer> The surface protective layer may further contain a resin other than the styrene-acrylic copolymer resin (B), such as a urethane resin, a polylactic acid resin, a polyamide resin, a vinyl chloride-acrylic copolymer resin, a castor oil resin, a rosin resin, a vinyl acetate resin, an ethylene-vinyl acetate copolymer resin, a vinyl acetate resin, an acrylic resin (which may be the same as or different from the <acrylic resin (A')> described below), a urethane-acrylic resin, a styrene-allyl alcohol copolymer resin, a styrene-maleic acid copolymer resin, a rosin-modified maleic acid resin, a dammar resin, and modified resins thereof. These resins may be used alone or in a mixture of two or more.

[0065] The styrene-acrylic copolymer resin (B) contained in the surface protective layer may be a commercially available product, for example, Joncryl 74J, Joncryl 537E, etc., manufactured by BASF.

[0066] <Additives contained in the surface protective layer> The surface protective layer of the present invention may contain various additives as required, such as dispersants, waxes, extender pigments, leveling agents, defoamers, film-forming assistants, water repellents, and release agents (silicone). Specifically, various additives can be added, such as a wax resin microparticle dispersion of a hydrocarbon wax such as polyethylene wax in order to improve abrasion resistance; extender pigments such as silica, barium sulfate, resin beads, calcium carbonate, talc, etc. in order to improve drying properties and coating film hiding properties; inorganic microparticles and adhesive resins (acrylic resins (which may be the same as or different from the <acrylic resin (B)> described below), vinyl acetate resins) in order to impart anti-slip properties; leveling agents in order to improve leveling properties; antifoaming agents in order to impart antifoaming properties; basic compounds such as sodium hydroxide, potassium hydroxide, etc. in order to impart re-solubility; and film-forming assistants. From the viewpoint of improving abrasion resistance, it is preferable to include a hydrocarbon wax such as polyethylene wax.

[0067] <Hydrocarbon wax such as polyethylene wax> The surface protective layer preferably contains a hydrocarbon wax such as polyethylene wax. This is for the purpose of improving the gloss of the surface and improving water resistance. The polyethylene wax referred to here is particulate and includes polyethylene obtained by the Fischer-Tropsch process. The average particle size of the polyethylene wax is preferably 0.05 to 10 μm, and more preferably 0.1 to 8 μm. The content of the polyethylene wax in the surface protective layer is preferably 0.1 to 15% by mass, more preferably 1 to 10% by mass, and even more preferably 6 to 10% by mass, based on 100% by mass of the surface protective layer. In addition, the hardness (penetration) at 25° C. as specified by JIS K2207 is preferably 0.5 to 12.

[0068] <Overcoat agent> The surface protective layer is preferably formed by an overcoat agent. The overcoat agent is preferably an aqueous overcoat agent. The overcoat agent contains a styrene-acrylic copolymer resin (B) and an aqueous medium, and preferably further contains polyethylene wax. The overcoat agent may further contain resins and additives other than the styrene-acrylic copolymer resin (B). From the viewpoint of printability, etc., the viscosity of the overcoat agent is preferably 20 to 200 mPa s.

[0069] The solid content of the styrene-acrylic copolymer resin (B) in the overcoat agent is preferably 25 to 100 mass %, more preferably 25 to 75 mass %, and particularly preferably 25 to 45 mass %, based on the total mass of the overcoat agent.

[0070] (aqueous medium) The overcoat agent preferably contains an aqueous medium. The main component of the aqueous medium is preferably water, but in addition to water, a water-soluble organic solvent can be used. Specifically, depending on the printing conditions (speed, plate depth, design, drying temperature), an alcohol-based organic solvent, a glycol-based organic solvent, etc. can be contained. The content of the aqueous medium is preferably 30% by mass or less based on the total amount of the overcoat agent. In the present invention, the term "mainly water" means that the content of water is the largest in the aqueous medium, and the term "water-soluble organic solvent" means that the solvent is liquid at 25° C. and has a solubility of 1% by mass or more in water at 25° C.

[0071] Examples of the alcohol-based organic solvent include methanol, ethanol, propanol, isopropanol, isobutanol, normal butanol, tertiary butanol, hexanol, octanol, and decanol.

[0072] Examples of the glycol-based organic solvent include ethylene glycol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, ethylene glycol monobutyl ether, ethylene glycol monooctyl ether, diethylene glycol, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monopropyl ether, diethylene glycol monobutyl ether, triethylene glycol, triethylene glycol monomethyl ether, triethylene glycol monoethyl ether, triethylene glycol monopropyl ether, triethylene glycol monobutyl ether, propylene glycol, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, dipropylene glycol, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol monopropyl ether, dipropylene glycol monobutyl ether, tripropylene glycol, tripropylene glycol monomethyl ether, tripropylene glycol monoethyl ether, tripropylene glycol monopropyl ether, tripropylene glycol monobutyl ether, and dibutyl glycol. These may be used alone or in combination of two or more.

[0073] <Method of manufacturing the overcoat agent> The overcoat agent can be obtained by feeding a resin solution, in which a resin is dissolved or dispersed in an organic solvent, and a solvent into an agitator equipped with an agitating blade, a rotor, etc., and mixing and stirring the solvent. There is no particular restriction on the stirring speed, and stirring can be performed at 50 to 2000 rpm. In order to improve the handling and coating properties of the overcoat agent, a solvent can also be appropriately added. From the viewpoint of printability and the like, the viscosity of the overcoat agent is preferably 50 to 300 mPa·s.

[0074] <Formation of surface protective layer> The surface protective layer can be formed, for example, by printing an overcoat agent on a paper substrate and then removing the volatile components. The printing method includes a flexographic printing method, in which, for example, the overcoat agent is diluted with a diluting solvent to a viscosity and concentration suitable for flexographic printing, and is supplied to each printing unit alone or in a mixture and applied. The surface protective layer can then be obtained by fixing the coating by drying in an oven or the like.

[0075] The packaging material may further have a printed layer formed by applying a printing ink onto the paper base material on the surface protective layer side. In the present application, the term "printing ink" refers to a material containing a colorant such as a pigment.

[0076] [Print layer] The printing layer is preferably located between the paper substrate and the surface protective layer and contains a colorant and an aqueous resin. The aqueous resin refers to a resin that can be dissolved or dispersed in water, and includes water-soluble resins and aqueous emulsion resins. Here, the aqueous emulsion resin refers to a resin that is insoluble or poorly soluble in water, but is dispersed and stabilized in water using a surfactant or the like.

[0077] When the printed layer contains an aqueous emulsion resin, the average particle size of the aqueous emulsion resin is preferably 10 to 500 nm, and more preferably 30 to 200 nm. When a printing ink is used to form the printed layer, the average particle size is the average particle size in the printing ink.

[0078] The thickness of the printed layer is preferably 0.1 to 10 μm, more preferably 0.3 to 6 μm, and particularly preferably 0.5 to 3 μm. In the present invention, not only a single printed layer but also a layer in which multiple printed layers are overlapped is regarded as the printed layer, and printed layers with different hues can be arbitrarily combined.

[0079] <Water-based resin contained in the printing layer> The content of the aqueous resin in the printed layer is preferably from 10 to 70% by mass, and more preferably from 30 to 50% by mass, based on the total mass of the printed layer. Examples of the aqueous resin include acrylic resins (excluding styrene-acrylic copolymer resins), styrene-acrylic copolymer resin (B'), styrene-maleic acid copolymer resin, acrylic resin (A'), urethane resin, polylactic acid resin, polyamide resin, vinyl chloride-acrylic copolymer resin, castor oil resin, rosin resin, vinyl acetate resin, ethylene-vinyl acetate copolymer resin, vinyl acetate resin, styrene-allyl alcohol copolymer resin, rosin-modified maleic acid resin, dammar resin, and modified resins thereof. Among them, it is preferable that the printed layer contains at least one resin selected from the group consisting of styrene-acrylic copolymer resin (B'), styrene-maleic acid copolymer resin, and acrylic resin (A'), and it is even more preferable that the printed layer contains styrene-acrylic copolymer resin (B'), because this improves the heat resistance of the packaging material.

[0080] The aqueous resin preferably has an acid group, and the acid group is preferably neutralized with a basic compound. Examples of the acid group include a hydroxyl group, an aldehyde group, a carbonyl group, and a carboxy group, and the like, and the carboxy group is preferred. Examples of the basic compound include an amine compound and an alkali metal compound.

[0081] Examples of the amine compound include ammonia, alkylamines such as diethylamine, triethylamine, and ethylenediamine, and alkanolamines such as monoethanolamine, ethylethanolamine, diethylethanolamine, diethanolamine, and triethanolamine. Examples of the alkali metal compound include sodium hydroxide and potassium hydroxide. These may be used alone or in combination of two or more.

[0082] (Styrene-acrylic copolymer resin (B')) The styrene-acrylic copolymer resin (B') may be a water-soluble styrene-acrylic copolymer resin (b'1) used as a water-soluble resin, or a styrene-acrylic copolymer resin (b'2) emulsion used as an aqueous emulsion resin. The styrene-acrylic copolymer resin (B') may be the same as or different from the styrene-acrylic copolymer resin (B).

[0083] (Water-soluble styrene-acrylic copolymer resin (b'1)) The water-soluble styrene-acrylic copolymer resin (b'1) preferably has an acid group, and in that case, the acid value is preferably 150 to 350 mgKOH / g, and more preferably 200 to 300 mgKOH / g. When the water-soluble styrene-acrylic copolymer resin (b'1) has an acid group and the acid value is within the above range, the recyclability and the number of foreign matter are good.

[0084] The water-soluble styrene-acrylic copolymer resin (b'1) preferably has a weight average molecular weight of 1500 to 50000, more preferably 1500 to 30000, and particularly preferably 1500 to 8000. The water-soluble styrene-acrylic copolymer resin (b'1) preferably has a glass transition temperature of 40 to 130° C., more preferably 60 to 100° C. When the water-soluble styrene-acrylic copolymer resin (b'1) has a weight average molecular weight and glass transition temperature within the above ranges, the water-soluble styrene-acrylic copolymer resin (b'1) has good blocking resistance.

[0085] The water-soluble styrene-acrylic copolymer resin (b'1) may be a commercially available product, for example, GL-2439 or YL-1098 manufactured by Seiko PMC Corporation.

[0086] (Styrene-acrylic copolymer resin (b'2) emulsion) The styrene-acrylic copolymer resin (b'2) preferably has an acid group, and in this case, the acid value is preferably 5 to 80 mgKOH / g, more preferably 20 to 60 mgKOH / g. When the styrene-acrylic copolymer resin (b'2) has an acid group and the acid value is in the above range, the recyclability and the number of impurities are good. The weight average molecular weight of the styrene-acrylic copolymer resin (b'2) is preferably 8,000 to 800,000, more preferably 20,000 to 500,000. The glass transition temperature of the styrene-acrylic copolymer resin (b'2) is preferably -20 to 60°C, more preferably 0 to 40°C. When the weight average molecular weight and glass transition temperature of the styrene-acrylic copolymer resin (b'2) are in the above ranges, the blocking resistance is good.

[0087] The print layer preferably contains both the water-soluble resin and the resin derived from the aqueous emulsion. The solid content ratio of the water-soluble resin and the aqueous emulsion resin is preferably water-soluble resin:aqueous emulsion resin=1:99 to 75:25, more preferably 1:99 to 55:45, and particularly preferably 15:85 to 35:65. With the above ratio, blocking resistance is good.

[0088] As the styrene-acrylic copolymer resin (b'2) emulsion, a commercially available product may be used, and examples thereof include JONCRYL 662, 669, 668, 665, 667, PDX 7198, 633-E, LMV7051, 90, and HPD396 manufactured by BASF.

[0089] (Styrene-maleic acid copolymer resin) The styrene-maleic acid copolymer resin preferably has an acid group, and in this case, the acid value is preferably 100 to 180 mgKOH / g, more preferably 120 to 160 mgKOH / g. When the styrene-maleic acid copolymer resin has an acid group and the acid value is in the above range, the recyclability and the number of impurities are good. The weight average molecular weight of the styrene-maleic acid copolymer resin is preferably 1500 to 50000, more preferably 4000 to 30000. The glass transition temperature of the styrene-maleic acid copolymer resin is preferably 40 to 120°C, more preferably 60 to 100°C. When the weight average molecular weight and glass transition temperature of the styrene-maleic acid copolymer resin are in the above range, the blocking resistance is good.

[0090] As the styrene-maleic acid copolymer resin, commercially available products may be used, for example, M-30 manufactured by Seiko PMC Corporation and Alastar series manufactured by Arakawa Chemical Industries, Ltd. can be used.

[0091] (Acrylic resin (A') (excluding styrene-acrylic copolymer resin (B')) The acrylic resin (A') preferably has an acid group, and in this case, the acid value is preferably 20 to 100 mgKOH / g, more preferably 40 to 80 mgKOH / g. When the acrylic resin has an acid group and the acid value is in the above range, the recyclability and the number of impurities are good. The weight average molecular weight of the acrylic resin (A') is preferably 1500 to 10000, more preferably 4000 to 30000. The glass transition temperature of the acrylic resin (A') is preferably 10 to 90°C, more preferably 30 to 70°C. When the weight average molecular weight and glass transition temperature of the acrylic resin (A') are in the above ranges, the blocking resistance is good.

[0092] The acrylic resin (A') may be a commercially available product, for example, X-310, VS-1057, GL-2439, or TS-1316 manufactured by Seiko PMC Corporation.

[0093] <Colorant contained in the printing layer> The printed layer preferably contains a colorant, and the content of the colorant in the total mass of the printed layer is preferably 1 to 60% by mass, and more preferably 30 to 50% by mass.

[0094] The colorant is preferably a pigment, and either an organic pigment or an inorganic pigment can be used. As the organic pigment, it is preferable to use a pigment made of an organic compound and / or an organic metal complex. As the inorganic pigment, it is preferable to use one containing titanium oxide.

[0095] Specific examples of organic pigments are shown by their Colour Index International (CI) numbers. Preferably, CI Pigment Red 57:1, CI Pigment Red 48:1, CI Pigment Red 48:2, CI Pigment Red 48:3, CI Pigment Red 146, CI Pigment Red 242, CI Pigment Yellow 83, CI Pigment Yellow 14, CI Pigment Orange 64, CI Pigment Orange 38, CI Pigment Orange 34, CI Pigment Orange 13, CI Pigment Yellow 180, CI Pigment Yellow 139, CI Pigment Red 185, CI Pigment Red 122, CI Pigment Red 178, CI Pigment Red 149, CI Pigment Red 144, CI Pigment Red 166, CI Pigment Violet 23, CI Pigment Violet 37, CI Pigment Blue 15, CI Pigment Blue 15:1, CI Pigment Blue 15:2, CI Pigment Blue 15:3, CI Pigment Blue 15:4, CI Pigment Blue 15:6, CI Pigment Green 7, CI Pigment Orange 34, CI Pigment Orange 64, and CI Pigment Black 7. These may be used alone or in combination of two or more.

[0096] (Inorganic pigments) Examples of inorganic pigments include titanium oxide, zinc oxide, zinc sulfide, barium sulfate, calcium carbonate, chromium oxide, silica, aluminum particles, mica, bronze powder, chrome vermilion, yellow lead, cadmium yellow, cadmium red, ultramarine, Prussian blue, red iron oxide, yellow iron oxide, iron black, titanium oxide, and zinc oxide. Aluminum can be either leafing or non-leafing type, with the non-leafing type being preferred.

[0097] <Additives contained in the printing layer> The printing layer of the present invention may contain various additives as necessary, such as dispersants, waxes, extender pigments, leveling agents, antifoaming agents, and film-forming assistants. Specifically, various additives can be added, such as a dispersion of wax resin particles such as polyethylene wax to improve abrasion resistance, extender pigments such as kaolin, aluminum hydroxide, clay, talc, etc. to improve drying properties and coating film hiding properties, inorganic particles and adhesive resins (acrylic resins (which may be the same as or different from the above-mentioned <acrylic resin>), vinyl acetate resins) to impart anti-slip properties, leveling agents to improve leveling properties, antifoaming agents to impart antifoaming properties, basic compounds such as sodium hydroxide, potassium hydroxide, etc. to impart re-solubility, and film-forming aids.

[0098] <Printing ink> The printed layer is preferably formed from a printing ink containing the above-mentioned colorant and the above-mentioned binder resin.

[0099] <Printing ink manufacturing method> The printing ink used to form the printing layer can be produced, for example, by dispersing a pigment in an organic solvent with a resin or the like using a disperser, and then mixing the resulting pigment dispersion with a resin, various additives, an organic solvent, and the like. As the disperser, a commonly used one, for example, a roller mill, a ball mill, a pebble mill, an attritor, or a sand mill, can be used. The particle size distribution of the pigment in the pigment dispersion can be adjusted by appropriately adjusting the size of the grinding media of the disperser, the filling rate of the grinding media, the dispersion processing time, the discharge speed of the pigment dispersion, the viscosity of the pigment dispersion, and the like. The viscosity of the printing ink at 25°C is preferably in the range of 50 mPa·s or more from the viewpoint of preventing the pigment from settling and dispersing appropriately, and 300 mPa·s or less from the viewpoint of workability and efficiency during ink production and printing.

[0100] <Formation of printing layer> The printing layer can be formed, for example, by printing with a printing ink on the paper substrate surface opposite to the heat seal layer, and then removing the volatile components. A suitable printing method is flexographic printing, in which, for example, the ink is diluted with a diluting solvent to a viscosity and concentration suitable for flexographic printing, and is supplied to each printing unit alone or in a mixture, and applied. The printing layer can then be obtained by fixing the coating by drying in an oven or the like.

[0101] In the present application, examples of the layered structure of the packaging material are as follows: In the following examples, " / " indicates the boundary between layers. Heat seal layer / barrier layer / paper base material / surface protection layer Heat seal layer / barrier layer / paper base material / printing layer / surface protection layer Heat seal layer / Paper base material / Barrier layer / Surface protection layer Heat seal layer / paper base material / barrier layer / printing layer / surface protection layer Heat seal layer / paper base material / printing layer / barrier layer / surface protection layer Heat seal layer / Paper base material containing barrier resin / Surface protection layer Heat seal layer / Paper base material containing barrier resin / Printing layer / Surface protection layer

[0102] <Difference in glass transition temperature between the resin contained in the heat seal layer and the resin contained in the surface protection layer> When reducing the amount of application of the heat seal layer, a uniform film can be formed by applying and drying the heat seal agent. If the solvent contained in the heat seal agent remains in the heat seal layer, blocking is likely to occur, but blocking resistance can be imparted to the packaging material by making the glass transition temperature of the resin contained in the surface protective layer higher than that of the resin contained in the heat seal layer. Considering the case where the heat seal layer and the surface protective layer contain two or more types of resin, the glass transition temperature Tg(D) of the heat seal layer and the glass transition temperature Tg(C) of the surface protective layer were calculated using the following formula.

[0103]

number

[0104] The difference between Tg(C) and Tg(D) is preferably 10 to 110° C., and more preferably 50 to 80° C. When it is within the above range, the balance between tack loss, load distribution, and film-forming properties is good, and therefore blocking resistance and heat sealability are improved.

[0105] <Amount of paper base material in packaging material> From the viewpoint of reducing the number of foreign matters, the content of the paper base material in the total amount of the packaging material is preferably 50 to 99 mass % or more, more preferably 65 to 95 mass % or more, and particularly preferably 80 to 90 mass %.

[0106] <Packaging bag> The packaging material in the present invention is cut to a predetermined size, and the edges are heat-sealed in a state where the heat-sealable layers are joined together to form a packaging bag. The heat-sealing temperature is preferably 50 to 250°C, and more preferably 80 to 180°C. The heat-sealing pressure is 1 to 5 kg / cm. 2The conditions are as follows. A packaging bag can be formed by folding one sheet of packaging material and heat sealing the edges, or by heat sealing two or more sheets of packaging material together. A packaging bag can also be formed by packaging the contents and then heat sealing all openings. This packaging bag can be widely used as a packaging bag for food, medicine, etc. EXAMPLES

[0107] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the present invention, parts and % represent parts by mass and % by mass unless otherwise noted. In addition, "NV." represents the mass % of non-volatile content.

[0108] <Preparation Example 1> Preparation of nitrocellulose resin solution NC1 57.1 parts of nitrocellulose nc1 (NV 70% (solvent: isopropyl alcohol), weight average molecular weight: 10,000, glass transition temperature: 155°C) was mixed and dissolved in 21.5 parts of ethyl acetate and 21.5 parts of isopropyl alcohol to obtain a NV 40% nitrocellulose resin solution (NC1).

[0109] <Preparation Example 2> Preparation of heat sealant HS1 91.7 parts of ethylene-vinyl acetate copolymer resin emulsion EVA1 (Sumitomo Chemical Co., Ltd., Sumikaflex S-410HQ, minimum film-forming temperature: 0°C, glass transition temperature: -18°C, vinyl alcohol resin emulsifier, NV. = 50%), 8.2 parts of a water / isopropyl alcohol mixed solvent (mass ratio 1:1), and 0.1 parts of BYK-024 (BYK, antifoaming agent) were added and mixed with stirring to obtain a heat sealing agent HS1.

[0110] <Preparation Examples 3-9> Preparation of heat sealant HS2-8 Heat sealing agents HS2 to HS8 were obtained in the same manner as in Preparation Example 2, except that the raw materials and compounding ratios shown in Table 1 were used. The properties of the raw materials used are as follows. Ethylene-vinyl acetate copolymer resin emulsion EVA2 (Sumitomo Chemical Co., Ltd., Sumikaflex S-305HQ, minimum film-forming temperature: 3°C, glass transition temperature: 7°C, vinyl alcohol resin emulsifier, NV=50%) Ethylene-vinyl acetate copolymer resin emulsion EVA3 (Sumitomo Chemical Co., Ltd., Sumikaflex S-328HQ, minimum film-forming temperature: 0°C, glass transition temperature: -5°C, vinyl alcohol resin emulsifier, NV=50%) Ethylene-vinyl acetate copolymer resin emulsion EVA4 (Sumitomo Chemical Co., Ltd., Sumikaflex S-408HQE, minimum film-forming temperature: 0°C, glass transition temperature: -30°C, vinyl alcohol resin emulsifier, NV=50%) Ethylene-vinyl acetate copolymer resin emulsion EVA5 (glass transition temperature: -47℃, NV.=50%) Ethylene-acrylic copolymer resin emulsion EAC1 (glass transition temperature: -15℃, NV.=50%) Ethylene-acrylic copolymer resin emulsion EAC2 (glass transition temperature: -30℃, NV.=50%) Acrylic resin emulsion AC1 (Seiko PMC, JE-1113, acid value: 42 mg KOH / g, glass transition temperature: -24°C, NV.=50%)

[0111] [Table 1]

[0112] <Preparation Example 10> Preparation of Barrier Coat Agent V1 50 parts of Kuraray Poval LM-20SO (manufactured by Kuraray Co., Ltd., saponification degree = 40 mol %, NV. = 100%), 25 parts of water, and 25 parts of isopropyl alcohol were added and heated and stirred at 80°C to obtain barrier coating agent V1.

[0113] <Preparation Example 11> Preparation of Barrier Coat Agent V2 25 parts of water and 25 parts of isopropyl alcohol were added to 50 parts of Soarnol D2908 (manufactured by Mitsubishi Chemical Corporation, ethylene content=29 mol%, NV.=100%), and the mixture was heated and stirred at 80° C. to obtain barrier coating agent V2.

[0114] Preparation Example 12: Preparation of overcoat agent X1 4.3 parts of water, 87.6 parts of styrene-acrylic copolymer resin emulsion SAC1 (acid value 108 mgKOH / g, glass transition temperature: 60°C, NV.40%), and 8.1 parts of polyethylene wax were added and mixed with stirring to obtain overcoat agent X1.

[0115] <Preparation Examples 13 to 17, Comparative Preparation Example 1> Preparation of overcoat agents X2 to 7 Overcoat agents V2 to V7 were obtained in the same manner as in Preparation Example 12, except that the raw materials and compounding ratios shown in Table 2 were used. The properties of the raw materials used are as follows. Styrene-acrylic copolymer resin emulsion SAC2 (acid value: 51 mg KOH / g, glass transition temperature: -10°C, NV.40%) Styrene-acrylic copolymer resin emulsion SAC3 (acid value: 38 mg KOH / g, glass transition temperature: 9°C, NV.40%) Styrene-acrylic copolymer resin emulsion SAC4 (acid value: 100mgKOH / g, glass transition temperature: 16℃, NV.40%) Styrene-acrylic copolymer resin emulsion SAC5 (acid value: 50 mg KOH / g, glass transition temperature: 96°C, NV.40%) [Table 2]

[0116] The following examples show methods for producing packaging materials.

[0117] <Evaluation of Residual Solvent Amount in Heat Seal Layer> Five 10 cm square pieces were cut out from the paper / barrier layer component of the obtained intermediate laminate. The five cut samples were heated at 180°C for 20 minutes, and the weight change of each sample before and after heating was calculated, and the average weight change of the five samples was taken as the residual solvent amount. Similarly, the residual solvent amount was calculated for the paper / barrier layer / heat seal layer component, and the residual solvent amount of the heat seal layer was calculated using Equation 5. (Formula 5) Residual solvent amount in heat seal layer (mg) = (average residual solvent amount in 5 samples of paper / barrier layer / heat seal layer) - (average residual solvent amount in 5 samples of paper / barrier layer part)

[0118] <Measurement of coating amount of heat seal layer> Five 10 cm square pieces were cut out from the heat seal layer / barrier layer / paper component of the obtained intermediate laminate, and five 10 cm square pieces were cut out from the barrier layer / paper component. The weight of each sample was measured, and the coating amount of the heat seal layer was calculated using Equation 6. (Formula 6) Coating weight of heat seal layer (mg) = (heat seal layer / barrier layer / average weight of 5 paper samples) - (barrier layer / average weight of 5 paper samples)

[0119] <Measurement of coating amount of barrier layer, printing layer and surface protective layer> For the barrier layer, the printing layer, and the surface protective layer, the coating weight was calculated in the same manner as in <Measurement of the coating weight of the heat seal layer>, except that the calculation formula and the cut-out location of the sample were different. The following kraft paper was used. Kraft paper: Kraft paper made from unbleached kraft pulp (manufactured by Nippon Paper Industries Co., Ltd., double-glazed kraft K, basis weight 70 g / m 2 , Fabric width: 100cm) <Formula 7> Coating weight of barrier layer (mg) = (barrier layer / average weight of 5 paper samples) / (average weight of 5 kraft paper samples) <Formula 8> Coating weight of printed layer (mg) = (average weight of 5 samples of barrier layer / paper / printed layer) / (average weight of 5 samples of barrier layer / paper) <Formula 9> Coating weight of surface protective layer (mg) = (average weight of five samples of heat seal layer / barrier layer / paper / printing / surface protective layer) / (average weight of five samples of heat seal layer / barrier layer / paper / printing layer)

[0120] <Example 1> Production of packaging material P1 Kraft paper: Kraft paper made from unbleached kraft pulp (manufactured by Nippon Paper Industries Co., Ltd., double-glazed kraft K, basis weight 70 g / m 2 A gravure printing machine equipped with a gravure plate having a depth of 50 μm was used to print a barrier coating agent V1 twice on a paper substrate (original width: 100 cm) at a printing speed of 50 m / min and an in-line oven temperature of 70°C to form a barrier layer on the entire surface of the paper substrate. Next, a gravure printing machine equipped with a gravure plate having a depth of 50 μm and having a non-image area on one half of the plate was used to print a heat seal agent HS1 twice on the barrier layer side of the paper substrate having a barrier layer at a printing speed of 50 m / min and an in-line oven temperature of 70°C to form a heat seal layer, thereby obtaining an intermediate laminate p1 having a heat seal layer / barrier layer / paper substrate structure. The intermediate laminate p1 has a mixture of a paper / barrier layer structure and a paper / barrier layer / heat seal layer structure, and a sample for evaluating the residual solvent amount can be obtained. The residual solvent amount in the heat seal layer of the intermediate laminate p1 was 1 mg. Next, the printing ink (Aqua PK Bio 23 Yellow, manufactured by Toyo Ink Co., Ltd., yellow ink; details of the contained resin will be described later) and the overcoat agent X1 were diluted with a mixed solvent of ethyl acetate:isopropyl alcohol = 7:3 (mass ratio), and the viscosity was adjusted to 15 seconds at 25 ° C. in a Zahn cup #3 (manufactured by Rigo Co., Ltd.). In the intermediate laminate p1, the diluted Aqua PK Bio 23 yellow was printed on the entire surface of the paper substrate at a printing speed of 50 m / min using a small flexiproof printer (flexographic printer) equipped with a 250 line / inch anilox roll and a solid plate made of photosensitive resin, and dried for 10 seconds with a 1200W dryer to form a printed layer. Next, on the printed layer, an overcoat agent X1 was printed on the entire surface of the printed layer at a printing speed of 50 m / min using a small flexiproof printer (flexographic printer) equipped with a 200 line / inch anilox roll and a solid plate made of photosensitive resin, to obtain a packaging material P1 having a heat seal layer / barrier layer / paper substrate / printed layer / surface protective layer configuration. In addition, in the coating of the surface protective layer, after securing the required amount of packaging material P1 in [Evaluation of packaging material], the coating was terminated, and a part of the heat seal layer / barrier layer / paper substrate / printed layer configuration was stored for measuring the coating amount. In the packaging material P1, the difference between Tg(C) and Tg(D) was 78°C.

[0121] The resins contained in the above printing ink Aqua PK Bio 23 Yellow are as follows. Styrene-acrylic copolymer resin emulsion SAC6 (acid value: 36 mg KOH / g, glass transition temperature: 14°C) Styrene-acrylic copolymer resin solution SAC7 (acid value: 213 mg KOH / g, weight average molecular weight: 8000, glass transition temperature: 73°C) The non-volatile content ratio of SAC6 to SAC7 is SAC4:SAC5=75:25.

[0122] <Examples 2 to 26> Production of packaging materials P2 to P26 Packaging materials P2 to P37 having the same configuration as in Example 1 were produced in the same manner as in Example 1, except that the heat seal agent, paper base material, barrier coating agent, printing ink, and overcoat agent shown in Table 3 were used.

[0123] <Comparative Example 1> Manufacturing of packaging material P27 Kraft paper: Kraft paper made from unbleached kraft pulp (manufactured by Nippon Paper Industries Co., Ltd., double-glazed kraft K, basis weight 70 g / m2 A polyethylene resin (melting point: 120°C) was hot-melt extrusion coated onto a 50 cm width from the edge of the paper substrate at a resin temperature of 330°C and a coating speed of 80 m / min to obtain an intermediate laminate p27 having a heat seal layer / paper substrate structure. The amount of residual solvent in the heat seal layer of the intermediate laminate p27 was 0 mg. Next, the printing ink (Aqua PK Bio 23 Yellow, manufactured by Toyo Ink Co., Ltd., yellow ink) and overcoat agent X1 were diluted with a mixed solvent of ethyl acetate:isopropyl alcohol = 7:3 (mass ratio), and the viscosity was adjusted to 15 seconds at 25 °C in a Zahn cup #3 (manufactured by Rigo Co., Ltd.). In the intermediate laminate p27, the diluted Aqua PK Bio 23 yellow was printed on the entire surface of the paper substrate at a printing speed of 50 m / min using a small flexiproof printer (flexographic printer) equipped with a 250 line / inch anilox roll and a solid plate made of photosensitive resin, and dried for 10 seconds with a 1200W dryer to form a printed layer. Next, on the printed layer, the overcoat agent X1 was printed on the entire surface of the printed layer at a printing speed of 50 m / min using a small flexiproof printer (flexographic printer) equipped with a 200 line / inch anilox roll and a solid plate made of photosensitive resin, to obtain a packaging material P27 having a paper substrate / printed layer / surface protective layer configuration. In addition, in the coating of the surface protective layer, after securing the required amount of packaging material P27 in [Evaluation of packaging material], the coating was terminated, and a part of the heat seal layer / paper substrate / printed layer configuration was stored for measuring the coating amount. In the packaging material P27, the difference between Tg(C) and Tg(D) was 185°C.

[0124] <Comparative Example 2> Manufacturing of packaging material P28 Kraft paper: Kraft paper made from unbleached kraft pulp (manufactured by Nippon Paper Industries Co., Ltd., double-glazed kraft K, basis weight 70 g / m 2A gravure printing machine equipped with a gravure plate with a plate depth of 50 μm was used to print the barrier coating agent V1 twice on a paper substrate (100 cm wide, 100 cm long) at a printing speed of 50 m / min and an in-line oven temperature of 70°C to form a barrier layer on the entire surface of the paper substrate. Next, a polyethylene resin (melting point: 120°C) was hot-melt extrusion coated on the barrier layer side of the paper substrate with a barrier layer in a width of 50 cm from the edge of the paper substrate at a resin temperature of 330°C and a coating speed of 80 m / min to obtain an intermediate laminate p28 having a heat seal layer / barrier layer / paper substrate structure. The intermediate laminate p28 has a mixture of a paper / barrier layer structure and a paper / barrier layer / heat seal layer structure, so that a sample for evaluating the residual solvent amount can be obtained. The residual solvent amount in the heat seal layer of the intermediate laminate p28 was 0 mg. Next, the printing ink (Aqua PK Bio 23 Yellow, manufactured by Toyo Ink Co., Ltd., yellow ink) and overcoat agent X1 were diluted with a mixed solvent of ethyl acetate:isopropyl alcohol = 7:3 (mass ratio), and the viscosity was adjusted to 15 seconds at 25 °C in a Zahn cup #3 (manufactured by Rigo Co., Ltd.). In the intermediate laminate p1, the diluted Aqua PK Bio 23 yellow was printed on the entire surface of the paper substrate at a printing speed of 50 m / min using a small flexiproof printer (flexographic printer) equipped with a 250 line / inch anilox roll and a solid plate made of photosensitive resin, and dried for 10 seconds with a 1200W dryer to form a printed layer. Next, on the printed layer, the overcoat agent X1 was printed on the entire surface of the printed layer at a printing speed of 50 m / min using a small flexiproof printer (flexographic printer) equipped with a 200 line / inch anilox roll and a solid plate made of photosensitive resin, to obtain a packaging material P28 having a paper substrate / printed layer / surface protective layer configuration. In addition, in the coating of the surface protective layer, after securing the required amount of packaging material P28 in [Evaluation of packaging material], the coating was terminated, and a part of the heat seal layer / barrier layer / paper substrate / printed layer configuration was stored for measuring the coating amount. In the packaging material P28, the difference between Tg(C) and Tg(D) was 185°C. <Comparative Examples 3 to 6> Manufacturing of packaging materials P29 to P32 Packaging materials P29 to P32 having the same configuration as in Example 1 were produced in the same manner as in Example 1, except that the heat sealant, paper base material, barrier coating agent, printing ink, and barrier coating agent shown in Table 4 were used.

[0125] [Table 3]

[0126] [Table 3]

[0127] [Table 4]

[0128] [Evaluation of packaging materials] The packaging materials P1 to 32 obtained in Examples 1 to 26 and Comparative Examples 1 to 6 were evaluated as described below. The results are shown in Tables 3 and 4. Note that in order to measure the amount of residual solvent, a portion of the packaging material did not have a heat seal layer, but this portion was not used in the following evaluation.

[0129] <Heat sealability evaluation> The obtained packaging material was cut into a size of 15 mm x 100 mm, folded so that the heat-sealed layers overlapped each other, and heat-sealed using the following equipment and conditions. Both unsealed ends were fixed to a small tensile tester to evaluate the heat-seal strength. A, B, and C are ranges that are acceptable for practical use. <Heat sealing conditions> Equipment: Heat seal tester manufactured by Tester Sangyo Co., Ltd., Seal width: from the folded part 10mm, heater temperature: 160℃, sealing pressure: 2kg / cm 2 , Sealing time: 1sec <Heat seal strength measurement conditions> Equipment: Intesco small tensile testing machine (model: IM-20), test piece width: 15 mm, Peeling mode: 90° peeling, tensile speed: 300mm / min Evaluation Criteria A. The heat seal strength is 3.5N or more. B. The heat seal strength is greater than 2.5N and less than 3.5N. C. The heat seal strength is 1.0N or more and less than 2.5N. D. The heat seal strength is less than 1.0 N.

[0130] <Recyclability> The obtained packaging material was cut into 3 cm square pieces, and the pieces were weighed to a total of 58 g and used as samples for testing. 1.5 L of 30°C hot water, 7 mL of 3.75% sodium hydroxide aqueous solution (0.5% to paper), and 7 mL of deinking agent (DI-7027 manufactured by Kao Corporation) diluted to 1.5% (0.2% to paper) were added to a 2 L pulper, and then the sample was added and stirred at 3000 rpm for 20 minutes. Two minutes after the start of stirring, the sample attached to the lid was washed into the tank with a small amount of water. After the disintegration was completed, the sample was concentrated to 625 g using a 150 mesh wire net.

[0131] 1350mL of purified water at room temperature was added to the 2L pulper and redisintegrated together with the concentrated sample for 1 minute, then the sample was transferred from the 2L pulper to a 10L bucket and warm water of 30°C ± 2°C was added to dilute to 5.4kg. Of this, 4.3kg was taken and stirred for 10 minutes with a J.TAPPI No.39 compliant floatator SF-25 manufactured by Kyokuto Shinko Co., Ltd. at a screw speed of 1500rpm and an air supply of 4L / min.

[0132] The sample in the flotator tank was collected and diluted with water to a total weight of 8 kg. An aluminum sulfate solution was then added to adjust the pH to 5.0 to 5.6, and the collected pulp was obtained.

[0133] A wet paper was made from the recovered pulp using a 150 mesh wire mesh in a hand paper machine (φ160 mm, manufactured by Kumagai Riki Kogyo Co., Ltd.) specified in JIS P8222, sandwiched between filter paper, and pressed for 5 minutes at a pressure of 410 kPa to dehydrate. The paper was then dried for 4 minutes at a surface temperature of 90°C using a rotary drum dryer. The weight after drying was adjusted to 60 g, and 5 sheets of recycled paper were made. The remaining recovered pulp was also dried under the same conditions as above to obtain dried pulp.

[0134] From the five sheets of recycled paper and the dried pulp obtained, impurities such as metal pieces that were apparently not derived from the heat seal layer, barrier layer, paper base material, printing layer, and surface protection layer were removed. The performance of the resulting recycled paper was evaluated by the following methods. The results are shown in Tables 3 and 4.

[0135] The pulp recovery rate was calculated for five sheets of recycled paper and dried pulp using the following formula, and the results were evaluated according to the following criteria. Note that A, B, and C are within the range where no practical problems occur. Equation 10 Paper base mass (g) = 70 (g / m 2 ) × {(total area of ​​58g sample (m 2 )} Equation 11 Pulp recovery rate (mass%) = {mass of 5 recycled paper sheets (g) + mass of dry pulp (g)} / mass of paper base material (g) Evaluation Criteria A. The pulp recovery rate is 95% by mass or more. B. The pulp recovery rate is 90% by mass or more and less than 95% by mass. C. The pulp recovery rate is 80% by mass or more and less than 90% by mass. D. The pulp recovery rate is less than 80% by mass.

[0136] <Evaluation of low number of foreign objects> The recycled paper produced above was measured using a dirt counter Spec*Scan 2000 manufactured by Apogee System Inc. to measure the dirt level to 0.3 mm. 2 Low debris count (pieces / 167cm) 2) was measured according to JIS P8208 Pulp - Foreign Matter Measurement Method. The measured value was the average value of the five sheets obtained. A, B, and C are practically acceptable ranges. A. Low number of foreign objects: 0 B. Low dust count: 1-2 pieces C. Low number of debris: 3-4 pieces D. Low dust count: 5 or more

[0137] <Evaluation of blocking resistance> The obtained packaging material was cut into two pieces of 40 mm square, and the heat seal layer surface of one packaging material piece was completely overlapped with the surface protection layer surface of the other packaging material piece, and the temperature was 40°C, humidity was 80% RH, and a load of 100 N / cm was applied. 2 After leaving it for 24 hours, the two overlapping packaging materials were peeled off, and the peeling state of the printed layer was visually observed and evaluated according to the following criteria. A, B, and C are ranges that are acceptable for practical use. Evaluation Criteria A. The amount of the printed layer transferred to the heat seal layer surface is less than 5% by area. B. The amount of the printed layer transferred to the heat seal layer surface is 5% or more by area and less than 10% by area. C. The amount of the printed layer transferred to the heat seal layer surface is 10% by area or more and less than 25% by area. D. The amount of the printed layer transferred to the heat seal layer surface is 25% or more by area.

[0138] <Oxygen barrier property evaluation> The obtained packaging material was subjected to oxygen transmission rate measurement according to a method in accordance with JIS K 7126-2:2006 and evaluated according to the following criteria, where A, B, and C are ranges that are acceptable for practical use. Evaluation Criteria A. Oxygen permeability is 100g / m 2 Less than 24 hours. B. Oxygen permeability is 100g / m 2 ·More than 24 hours, 1000g / m 2 Less than 24 hours. C. Oxygen permeability is 1000g / m 2 ·More than 24 hours, 10000g / m 2Less than 24 hours. D. Oxygen permeability is 10,000g / m 2 -24 hours or more.

[0139] From the above results, Comparative Examples 1 and 2 did not satisfy the requirements for heat sealability, recyclability, and low number of foreign matter because the heat seal layer contained polyethylene resin. Furthermore, Comparative Example 1 did not satisfy the oxygen barrier property because it did not have a barrier layer. Comparative Example 3 had a coating amount of 1 g / m 2 In Comparative Example 4, the coating amount of the heat seal layer was 18 g / m 2 Since the content of the styrene-acrylic copolymer resin (B) in the surface protective layer was not included, the recyclability, low number of foreign matter, and blocking resistance were not satisfied. Since the barrier layer was not included in Comparative Example 5, the oxygen barrier property was not satisfied. Since the surface protective layer was not included in Comparative Example 6, the low number of foreign matter and blocking resistance were not satisfied. On the other hand, in the examples, the heat seal layer contains an ethylene-vinyl acetate copolymer resin, the surface protective layer contains a styrene-acrylic copolymer resin (B), and the range of the coating amount of the heat seal layer is satisfied, so that the heat sealability, recyclability, low number of foreign matter, blocking resistance, and oxygen barrier properties are good. In particular, the coating amount of the heat seal layer is 5 g / m 2 In Example 1, in which the difference between the Tg(D) of the heat seal layer and the Tg(C) of the surface protective layer was 78°C, the surface protective layer contained polyethylene wax, and the barrier layer was located on the heat seal side, the film had excellent heat sealability, recyclability, low foreign matter count, blocking resistance, and oxygen barrier property.

Claims

1. A method for producing a packaging material having a heat seal layer, a barrier layer, a paper substrate, and a surface protective layer, comprising the steps of: An aqueous heat-sealing agent containing an acrylic resin (A) and / or an ethylene-vinyl acetate copolymer resin is applied to one side of a paper substrate having a barrier layer, and the coating amount is 1 to 18 g / m. 2 forming a heat seal layer; and applying an aqueous overcoat agent containing an aqueous styrene-acrylic copolymer resin (B) by flexographic printing onto the other surface of the paper base material having the barrier layer to form a surface protective layer.

2. 2. The method for producing a packaging material according to claim 1, wherein the glass transition temperature Tg(C) of the surface protective layer is higher than the glass transition temperature Tg(D) of the heat seal layer, and the difference between Tg(C) and Tg(D) is 10° C. or more.

3. A method for producing a packaging material as described in claim 1, wherein the aqueous overcoat agent further contains a hydrocarbon wax.

4. 4. The method for producing a packaging material according to claim 3, wherein the hydrocarbon wax has a hardness (penetration) at 25° C. as specified in JIS K2207 of 0.5 to 12.

5. A method for manufacturing a packaging material as described in claim 1, wherein, in the process of forming a heat seal layer, the heat seal layer is placed on the side of a paper base material having a barrier layer, the side having the barrier layer.

6. The method for producing a packaging material according to claim 1, wherein the barrier layer comprises a vinyl alcohol resin and / or an ethylene-vinyl alcohol copolymer resin.

7. The method for producing a packaging material according to claim 1 , wherein the content of the paper base material in the total amount of the packaging material is 50% by mass or more.

8. A method for producing a packaging material as described in claim 1, wherein the aqueous heat sealing agent further contains an emulsifier.

9. A method for producing a packaging bag formed from a packaging material produced by the method for producing a packaging material according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Recyclable transparent barrier laminate

    JP2003154609A

  • Composition for planographic printing liquid, and planographic printing liquid using the same

    JP2010006993A

  • Lithographic printing liquid composition, and lithographic printing liquid using this

    JP2010024331A

  • Laminate and packaging product containing the same

    JP2018051796A

  • Packaging material and packaging product

    JP2020055171A